DETERMINASI AKUNTABILITAS PENGELOLAAN DANA DESA DI DESA KALIKAJAR KECAMATAN KALIGONDANG KABUPATEN PURBALINGGA - Anjani, Lulu Alfiatun; Maharani, Destin Alfianika; Khusnia, Aulia Nisa (J-LEE - Journal of Law, English, and Economics, 2024)
Accountability is a form of one’s accountability to parties entitled to information about performance in carrying out tasks. This research is motivated by corruption cases that occurred in Indonesia which caused the country to experience enormous losses. State losses due to acts of corruption committed by village officials reached IDR 111 billion. This study aims to find out how accountable the management of Kalikajar village’s fund, Kaligondang sub-district, Purbalingga regency. This type of research is a case study using a descriptive analysis approach. The researcher used observation, documentation and interviews as the data collection techniques. The results of this study indicate that accountability for managing village funds in Kalikajar village has not been fully implemented in an accountable manner. At the planning, administration, reporting and accountability stages have been carried out in accordance with applicable procedures. Meanwhile, at the implementation stage it has not been carried out in an accountable manner because at the implementation stage the village community is only involved in terms of village development.